The Validity of Integrated Islamic Online Biology Quiz Using Quizizz Application on Plantae Subject - Fatikhatun Nikmatus Sholihah; Hasna Mudzaqqiroh; Muhamad Khoirur Roziqin (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Islamic values integrated Biology online quiz is a media developed through the quizizz online application as a supporting medium for learning biology which aims to provide integrated Islamic plantae material tests. The purposes of this study were to determine the validity of Islamic integrated biology online quizzes according to material experts and learning media experts. The objectives to be achieved are as follows: 1) describe the results of the validation of the Islamic values online integrated biology quiz using the quiz application on the Plantae material, 2) describe the results of the validation of the Islamic integrated biology online quiz using the quiz application on the plantae material according to media experts. This type of research is development research using a 4-D development model. The research instrument used is in the form of validation questionnaires for expert material and learning media. Data analysis techniques in the form of validation of questionnaire results y expert material and learning media. The results showed that online quizzes using Islamic integrated quiz applications had a validity percentage of 80% and learning media of 75%. This shows that Islamic integrated online quizzes can be used as a measure of valid Islamic integrated plantae material and can be used as learning suggestions.